Manajemen Sarana dan Prasarana Ruang Kelas dalam Mendukung Pembelajaran di MAN 2 Karawang - Khusnul Khotimah Dewi; Alisa Nuraeni; Maulana Agung Syaifie; Hinggil Permana (Lembaga Pengembangan Kinerja Dosen, 2025)
The quality of classroom facilities and infrastructure plays an important role in creating an optimal learning environment. Adequate facilities can improve student comfort, motivation, and learning outcomes. This study uses a qualitative approach with a case study method to explore the condition of classrooms at MAN 2 Karawang. Data were collected through observation, interviews, and documentation to gain a deeper understanding of the existing facilities. The findings of the study indicate that lighting and ventilation in the classrooms are adequate, and supported by academic props that support the learning process. However, there are several obstacles, such as limited room cooling systems and bureaucratic obstacles in maintaining facilities. In addition, the management of facilities and infrastructure by the SARPRAS team has not been optimal due to budget constraints. Therefore, it is necessary to continuously improve and repair facilities to support a more effective and comfortable learning process for students.